Psycho-social factors as correlate of health care seeking behaviour among pregnant and nursing mothers in Osun East Senatorial District, Nigeria - Oyesegun, Oyerinde, Olufemi; Olanrewaju, Oniyangi, Shuaib; Olaniyi, Fagbamila, Sayofunmi; Anike, Adebowale, Grace (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
his study examined psycho-social factors as correlate of health care seeking behaviour among pregnant and nursing mothers in Osun East Senatorial District of Osun State. A descriptive research of survey type was adopted for the study. Multistage sampling technique was used to select 150 subjects using purposive, simple random and stratified sampling techniques. A structured questionnaire was used, a reliability coefficient of 0.87r was observed. The paper was however concluded and appropriate recommendations were made among which are; pregnant and nursing mothers should be educated since education affect individual level of understanding and should focus on the need for antenatal and post natal to safeguard the health of the mother and that of the unborn child and health facilities and services for health care should be subsidized for the benefit of the poor and possibly rich pregnant and nursing mothers.